A method for manufacturing a composite of a one-way flow nonwoven fabric and a water absorbing paper
Patent Information
- Application Number
- CN202611100885.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-30
AI Technical Summary
现有同类复合材料在结构设计与制备工艺上存在诸多缺陷,难以满足实际使用需求
1、本发明通过结构创新与工艺优化,有效克服现有技术缺陷,赋予复合材料优异的综合使用性能;采用梯度针刺与梯度亲水整理相结合的方式,使无纺布形成稳定的纤维密度梯度与亲水梯度,构建定向液体传导通道,实现液体快速单向渗透,有效抑制横向扩散与反向回渗,提升使用干爽性。
Smart Images

Figure REF-OBJ-1784794996965-000001
Abstract
Description
Technical Field
[0001] This invention relates to the field of composite material preparation technology, specifically to a method for preparing a composite of unidirectional nonwoven fabric and absorbent paper. Background Technology
[0002] The fields of hygiene care and disposable absorbent materials place stringent requirements on liquid conductivity, absorption, and water-locking properties. Materials composed of unidirectional nonwoven fabric and absorbent paper are currently the core substrate for high-end absorbent products. Existing similar composite materials suffer from numerous defects in structural design and manufacturing processes, making it difficult to meet practical application needs.
[0003] Most current nonwoven fabrics use a uniform fiber structure and conventional hydrophilic finishing, which cannot form directional flow channels. Liquids tend to linger on the surface, spread laterally, or seep back, resulting in reduced user comfort. Traditional absorbent paper is mostly made from pure wood pulp without efficient modification treatment, resulting in limited absorbency and water retention capacity. After liquid absorption, backflow is likely to occur, affecting safety during use.
[0004] Existing composite processes mostly employ single hot-pressing or single adhesive bonding methods, resulting in insufficient interfacial bonding strength. This leads to delamination and detachment during use, affecting material stability. Furthermore, conventional fiber ratios do not consider flowability, breathability, and biodegradability, resulting in limited overall material functionality. Some substrates lack antibacterial treatment, making them susceptible to microbial growth with long-term use, posing hygiene and safety risks. In addition, existing preparation processes lack synergistic adaptation between gradient structures and composite processes, failing to simultaneously achieve unidirectional flowability, efficient water absorption, strong bonding, and good breathability, thus limiting the application of composite materials in high-end nursing scenarios.
[0005] To solve the above-mentioned technical problems, it is urgent to develop a unidirectional nonwoven fabric and absorbent paper composite technology with reasonable structural design, perfect preparation process and excellent comprehensive performance. Summary of the Invention
[0006] The primary objective of this invention is to provide a method for preparing a composite of unidirectional nonwoven fabric and absorbent paper.
[0007] A further objective of this invention is to provide a composite material of unidirectional nonwoven fabric and absorbent paper, which is composed of a unidirectional nonwoven fabric layer and a modified absorbent paper layer; the unidirectional nonwoven fabric layer has a gradient structure with a high hydrophilicity on the upper surface and a low hydrophilicity on the lower surface; the modified absorbent paper layer contains a surface-modified superabsorbent resin; the two layers are combined by a combination of hot-pressing and hydrophilic adhesive bonding.
[0008] Preferably, the raw materials for the unidirectional nonwoven fabric layer are kapok fiber, hydrophilic modified polypropylene fiber, and polylactic acid fiber. Based on a total raw material mass of 100 parts, the kapok fiber is 25-35 parts, the hydrophilic modified polypropylene fiber is 45-55 parts, and the polylactic acid fiber is 15-25 parts.
[0009] Preferably, the weight ratio of softwood pulp to hardwood pulp in the modified absorbent paper layer is 20:80-30:70; the surface-modified superabsorbent resin is a sodium acrylate-acrylamide copolymer resin modified with silane coupling agent KH-550.
[0010] A method for preparing the composite material includes the following steps: (1) Preparation of unidirectional nonwoven fabric: the fibers are mixed, opened and combed into a fiber web, and then the fiber felt is obtained by four gradient needle punches. The fiber felt is then impregnated with an antibacterial hydrophilic finishing agent and dried. (2) Modification of absorbent paper: Wood pulp is crushed, ground and mixed into pulp, wet strength agent, softener and surface-modified superabsorbent resin are added, and modified absorbent paper is obtained by wet forming, pressing and drying. (3) Composite molding: The lower surface of the unidirectional nonwoven fabric is bonded to the upper surface of the modified absorbent paper, and the composite intermediate is obtained by hot pressing and bonding with a hydrophilic adhesive; (4) Finishing: The composite intermediate is shaped, trimmed, and rolled to obtain the finished product.
[0011] Preferably, the fiber opening speed is 700-900 r / min, the opening time is 12-18 min, the carding speed is 2-4 m / min, and the carding spacing is 0.25-0.35 mm.
[0012] Preferably, the acupuncture frequency of the four-level gradient acupuncture is 180-220 times / min, and the acupuncture needle density is 1200-1500 needles / m². 2 The depth of acupuncture decreases gradually, while the number of acupuncture points increases gradually.
[0013] Preferably, the antibacterial hydrophilic finishing agent is composed of 25%-30% organosilicon quaternary ammonium salt, 30%-35% hydrophilic amino silicone oil, and 40% water by weight; the impregnation temperature is 40-50℃, and the impregnation time is 20-25 min.
[0014] Preferably, the wood pulp is milled to a beating degree of 40-45°SR; the amount of surface-modified superabsorbent resin added is 8-15 parts of the total mass of the wood pulp.
[0015] Preferably, the hydrophilic adhesive is a water-based polyurethane adhesive, applied using a textured coating method, with a coating amount of 3-7 g / m². 2 The hot-pressing temperature is 120-150℃, the hot-pressing pressure is 0.1-0.3MPa, and the hot-pressing time is 8-12s.
[0016] Preferably, the composite intermediate is set at a temperature of 90-110℃ for 15-20 minutes and a winding tension of 50-60N.
[0017] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention effectively overcomes the defects of existing technologies through structural innovation and process optimization, endowing composite materials with excellent comprehensive performance. By combining gradient needle punching and gradient hydrophilic finishing, the nonwoven fabric forms a stable fiber density gradient and hydrophilic gradient, constructs directional liquid conduction channels, realizes rapid one-way liquid penetration, effectively inhibits lateral diffusion and reverse backflow, and improves dryness during use.
[0018] 2. This invention specifically modifies absorbent paper by introducing functional components, which significantly improves the material's water absorption capacity and water retention ability, ensuring stable retention of liquid after absorption and reducing the risk of backflow.
[0019] 3. This invention employs a process that combines hot-pressing lamination with hydrophilic adhesive lamination, enabling the nonwoven fabric and absorbent paper to form a tight, gapless composite interface, which significantly improves the interfacial bonding strength, prevents delamination during use, and ensures the stability of the material structure.
[0020] 4. This invention utilizes a multi-component fiber synergistic combination to optimize the internal pore structure of the material, ensuring airflow performance while improving breathability and enhancing user comfort. Through an antibacterial finishing process, the material is endowed with excellent antibacterial properties, inhibiting microbial growth and improving hygiene and safety levels.
[0021] 5. The various preparation steps of this invention are coordinated and adapted, the process is highly controllable, the resulting composite material has stable dimensions and excellent balanced properties, which can meet the needs of high-end hygiene and care products, broaden the application scenarios of absorbent composite materials, and have good practical value and market prospects. Detailed Implementation
[0022] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0023] Example 1:
[0024] Preparation of unidirectional flow nonwoven fabric: Kapok fiber, hydrophilic modified polypropylene fiber, and polylactic acid fiber were selected as raw materials, with a total raw material mass of 100 parts, including 30 parts of kapok fiber, 50 parts of hydrophilic modified polypropylene fiber, and 20 parts of polylactic acid fiber.
[0025] The kapok fiber selected is natural kapok fiber with a length of 3-5 mm and a fineness of 1.2 dtex. The hydrophilic modified polypropylene fiber is polypropylene fiber modified with polyethylene glycol and a hydrophilic group grafting rate of 15%. The polylactic acid fiber is biodegradable polylactic acid fiber with a fineness of 1.5 dtex and a length of 4 mm. The above raw materials are fed into an opening machine for opening treatment at an opening speed of 800 r / min for 15 min to ensure that the raw materials are fully opened and free of lumps.
[0026] The opened mixed fibers are fed into a carding machine at a carding speed of 3 m / min and a carding spacing of 0.3 mm to form a uniform fiber web with a thickness controlled at 0.4 mm. The carded fiber web is then subjected to multi-stage gradient needle punching at a needle punching frequency of 200 times / min and a needle density of 1200 needles / m². 2 A total of four needle-punching processes were performed. The first needle-punching depth was equal to the total height of the fiber web, with 3 needle-punching cycles. The second needle-punching depth was 11 / 12 of the total height of the fiber web, with 5 needle-punching cycles. The third needle-punching depth was 10 / 12 of the total height of the fiber web, with 7 needle-punching cycles. The fourth needle-punching depth was 9 / 12 of the total height of the fiber web, with 9 needle-punching cycles. Through gradient needle-punching, a fiber density gradient was formed between the upper and lower layers of the fiber web, laying the structural foundation for subsequent gradient hydrophilic finishing, resulting in a pre-formed fiber felt. The fiber felt was then placed in a hydrophilic and hydrophobic gradient finishing tank and impregnated with an antibacterial hydrophilic finishing agent. The antibacterial hydrophilic finishing agent was composed of 25% organosilicon quaternary ammonium salt, 35% hydrophilic amino silicone oil, and 40% water by mass percentage. The organosilicon quaternary ammonium salt was a cationic organosilicon quaternary ammonium salt with a molecular weight of 2000, and the hydrophilic amino silicone oil was a modified silicone oil with an ammonia value of 0.3 mmol / g. Impregnation temperature 45℃, impregnation time 20min, hydrophilic finishing agent adhesion amount on the surface of fiber felt 8g / m 2 The amount of hydrophilic finishing agent adhering to the lower surface is 3g / m. 2 Gradient impregnation creates a gradient structure in the nonwoven fabric, with a highly hydrophilic upper surface and a less hydrophilic lower surface, ensuring unidirectional liquid conduction.
[0027] After impregnation, the fabric is sent to a drying device at a temperature of 120℃ for 30 minutes, until the moisture content of the fiber felt is below 3%, resulting in a unidirectional nonwoven fabric with a basis weight of 40 g / m². 2 Thickness 0.3mm.
[0028] Modified absorbent paper: Softwood pulp and hardwood pulp were selected as the base materials for absorbent paper, with a weight ratio of softwood pulp to hardwood pulp of 30:70 and a total weight of 100 parts. The softwood pulp used was bleached softwood pulp with a freeness of 35°SR, and the hardwood pulp used was bleached hardwood pulp with a freeness of 28°SR. The pulps were fed into a pulper with a pulping concentration of 5 wt%, a pulping time of 15 minutes, and a pulping speed of 1200 r / min to ensure that the pulp was fully broken down into individual fibers.
[0029] After pulping, the pulp is fed into a refiner with a refinement power of 320kW. During refinement, the pulp throughput is 1950L / min, the refinement concentration is 4.0wt%, and refinement is carried out until the pulp freeness is 45°SR, so that the pulp forms uniform fiber flocs, improving the forming and water absorption properties of the absorbent paper. After refinement, the pulp is mixed, and additives are added during the mixing process. The additives consist of a wet strength agent and a softener. The wet strength agent is polyamide epichlorohydrin resin, added at 1.5 parts by the total mass of wood pulp. The softener is fatty alcohol polyoxyethylene ether, added at 0.8 parts by the total mass of wood pulp. At the same time, a self-made surface-modified superabsorbent resin is added. The superabsorbent resin is sodium acrylate-acrylamide copolymer modified resin, with the surface modified by silane coupling agent KH-550, and a particle size of 100 mesh. The amount added is 8 parts by the total mass of wood pulp. The stirring speed is 800r / min, and the stirring time is 20min to ensure that the additives are evenly dispersed in the pulp. The pulp was wet-laid onto a wire with a wire concentration of 0.7 wt% and a forming speed of 2 m / min. The resulting absorbent paper had a relative moisture content of 65%, with the wet top layer having a dry basis weight of 30 g / m². 2 The wet bottom paper has a basis weight of 40 g / m² after drying. 2 .
[0030] The wet absorbent paper is fed into a pressing device with a pressing pressure of 0.3 MPa and a pressing speed of 2 m / min. After pressing, the moisture content of the wet absorbent paper drops to below 40%. It is then fed into a drying device with a drying temperature of 110℃ and a drying time of 25 min. The paper is dried until the relative moisture content is 7%, resulting in modified absorbent paper with a longitudinal tensile strength of 2.5 N / 15 mm and a transverse tensile strength of 1.8 N / 15 mm.
[0031] Composite molding: The lower surface of the prepared unidirectional nonwoven fabric was bonded and aligned with the upper surface of the modified absorbent paper, with the bonding deviation controlled within ±0.5 mm. A combination of hot-pressing and hydrophilic adhesive bonding was used. The hydrophilic adhesive was a water-based polyurethane adhesive with a solid content of 30% and a viscosity of 2000 mPa·s. The adhesive coating amount was 5 g / m². 2The coating method is anilox coating with an anilox roller mesh count of 120. The hot-pressing composite temperature is 130℃, the hot-pressing pressure is 0.2MPa, the hot-pressing speed is 1.5m / min, and the hot-pressing time is 10s. Through hot pressing, the adhesive is fully melted, achieving molecular-level bonding between the unidirectional nonwoven fabric and the absorbent paper, ensuring that there are no gaps at the composite interface.
[0032] Post-editing: The composite material is fed into a setting device at a setting temperature of 100℃ for 15 minutes to eliminate internal stress generated during the composite process and improve the dimensional stability of the composite material. After setting, the edges are trimmed with a width controlled within ±0.2mm. Finally, the material is wound at a speed of 1.5m / min and a tension of 50N to obtain a composite product of unidirectional nonwoven fabric and absorbent paper with a width of 1000mm and a roll diameter of 300mm.
[0033] Example 2:
[0034] This embodiment focuses on optimizing the fiber composition of the unidirectional flow-guiding nonwoven fabric to improve its flow-guiding and breathability performance. It clarifies the method of adding bamboo fiber and the details of parameter adaptation. The remaining process steps are optimized and adjusted based on Embodiment 1.
[0035] Preparation of unidirectional flow nonwoven fabric: Kapok fiber, hydrophilic modified polypropylene fiber, polylactic acid fiber, and bamboo fiber were selected as raw materials, with a total raw material mass of 100 parts, including 60 parts of kapok fiber, 20 parts of hydrophilic modified polypropylene fiber, 10 parts of polylactic acid fiber, and 10 parts of bamboo fiber.
[0036] The bamboo fiber used is natural bamboo fiber with a length of 4-6 mm and a fineness of 1.0 dtex. It undergoes high-temperature steaming and degumming to remove impurities and lignin. The specifications of the remaining raw materials are the same as in Example 1. The above raw materials are fed into an opening machine for opening treatment at a speed of 700 r / min for 18 minutes to ensure thorough mixing of the bamboo fiber with other fibers without agglomeration. The opened mixed fibers are then fed into a carding machine at a carding speed of 3 m / min and a carding spacing of 0.25 mm to form a uniform fiber web with a thickness controlled at 0.45 mm. The needle punching process is adjusted to a needle punching frequency of 180 times / min and a needle density of 1500 needles / m². 2 A total of four needle-punching processes were performed. The first needle-punching depth was equal to the total height of the fiber web, with two needle-punching passes. The second needle-punching depth was 11 / 12 of the total height of the fiber web, with four needle-punching passes. The third needle-punching depth was 10 / 12 of the total height of the fiber web, with six needle-punching passes. The fourth needle-punching depth was 9 / 12 of the total height of the fiber web, with eight needle-punching passes. The addition of bamboo fiber further optimized the gradient structure of the fiber web. The hydrophilic and hydrophobic gradient finishing process was the same as in Example 1. After drying, a unidirectional nonwoven fabric with a basis weight of 45 g / m² was obtained. 2Thickness 0.35mm.
[0037] Water-absorbing paper modification, composite molding, and finishing: The absorbent paper modification process was completely consistent with that of Example 1, ensuring that the single variable was the fiber ratio, and clearly demonstrating the role of bamboo fiber in improving the flow and breathability. During the composite molding process, the adhesive coating amount was adjusted to 5.5 g / m². 2 To adapt to changes in the basis weight of the unidirectional nonwoven fabric, the composite strength is ensured. The finishing process is the same as in Example 1, but the winding tension is adjusted to 55N to adapt to changes in the basis weight of the finished product, resulting in the composite finished product.
[0038] Example 3:
[0039] This embodiment focuses on optimizing the absorbent paper modification process to improve its absorbency and water-locking performance. It clarifies the adjustment basis for the wood pulp ratio, additive ratio, and superabsorbent resin dosage, adapts to the flow rate of Embodiment 2, and the remaining process steps are adapted in conjunction with Embodiment 2.
[0040] Preparation of unidirectional flow nonwoven fabric: Completely consistent with Example 2, ensuring that the single variable is the absorbent paper modification process, clarifying the impact of absorbent paper modification on water-locking performance, and achieving coordinated adaptation of process parameters.
[0041] Modified absorbent paper: Softwood pulp and hardwood pulp were selected as the raw materials for the absorbent paper substrate, with a weight ratio of softwood pulp to hardwood pulp of 20:80 and a total mass of 100 parts. The specifications of the softwood pulp and hardwood pulp were the same as in Example 1. The pulping and refining processes were the same as in Example 1, refining to a pulp freeness of 40°SR. The addition of superabsorbent polymer (SAP) was adjusted to improve the bonding performance between the pulp and SAP. During the pulp preparation process, the additive ratios were adjusted: the wet strength agent was added at 2.0 parts by the total mass of the wood pulp, the softener at 0.5 parts by the total mass of the wood pulp, and the amount of self-made surface-modified SAP was adjusted to 15 parts by the total mass of the wood pulp. The stirring speed was 900 r / min, and the stirring time was 25 min to ensure uniform dispersion of the SAP. The wet web forming process was adjusted to a web concentration of 0.6 wt% and a web forming speed of 1.8 m / min. The resulting paper has a relative moisture content of 70%, with the wet surface layer having a dry basis weight of 25 g / m². 2 The wet bottom paper has a basis weight of 45 g / m² after drying. 2 .
[0042] The pressing and drying processes are the same as in Example 1. The paper is dried until the relative moisture content of the absorbent paper is 6%, thus obtaining the modified absorbent paper.
[0043] Composite molding and finishing: During the composite molding process, the hot pressing temperature is adjusted to 135℃ to adapt to the change in the weight of the absorbent paper and ensure a tight bond at the composite interface.
[0044] The finishing process is the same as in Example 2, resulting in a composite finished product.
[0045] Example 4:
[0046] This embodiment focuses on optimizing the composite molding process and antibacterial modification to improve composite strength and overall performance. It clarifies the details of finishing agent ratio, composite parameters and antibacterial treatment to meet the needs of high-end scenarios. The remaining process steps are adapted in conjunction with those in Embodiment 3.
[0047] Preparation of unidirectional flow nonwoven fabric: The fiber ratio is the same as in Example 2, and the opening, carding, and needle punching processes are also the same as in Example 2. The antibacterial hydrophilic finishing agent ratio of the hydrophilic and hydrophobic gradient finishing tank is adjusted to a mixture of 30% organosilicon quaternary ammonium salt, 30% hydrophilic amino silicone oil, and 40% water by mass percentage. The specifications of the organosilicon quaternary ammonium salt and hydrophilic amino silicone oil are the same as in Example 1, which improves the antibacterial properties.
[0048] The impregnation temperature was adjusted to 50℃, the impregnation time was extended to 25 minutes, and the amount of hydrophilic finishing agent adhering to the surface of the fiber felt was adjusted to 10 g / m². 2 The amount of hydrophilic finishing agent adhering to the lower surface was adjusted to 4 g / m. 2 The gradient hydrophilic structure is further enhanced, and the drying process is the same as in Example 2, to obtain an antibacterial unidirectional flow nonwoven fabric with an antibacterial rate of over 90%.
[0049] Modified absorbent paper: Completely consistent with Example 3, ensuring that the single variable is the composite process and the post-processing process, and clarifying the impact of composite process adjustment on overall performance.
[0050] Composite molding: The bonding and alignment method is the same as in Example 3, except that the hydrophilic adhesive is changed to a mixture of water-based polyurethane adhesive and polyethylene glycol in a ratio of 8:2. The polyethylene glycol used is polyethylene glycol with a molecular weight of 400. The adhesive has a solid content of 35%, a viscosity of 2500 mPa·s, and the adhesive coating amount is adjusted to 7 g / m². 2 The coating method remains the same: textured coating. The hot-pressing composite process was adjusted to a hot-pressing temperature of 150℃, a hot-pressing pressure of 0.3MPa, a hot-pressing speed of 1.2m / min, and a hot-pressing time of 12s, further improving the bonding strength of the composite interface. The composite peel strength was increased by 13.3% compared to Example 3.
[0051] Post-editing: The composite material is then fed into a setting device, where the setting temperature is adjusted to 110℃ and the setting time is extended to 20 minutes to further improve dimensional stability. After setting, the edges are trimmed, and the material is then sent to an antibacterial treatment tank for spraying with a 0.5% chitosan antibacterial solution. The chitosan used is deacetylated chitosan with a molecular weight of 50,000, and the spraying rate is 3 g / m³. 2 The spraying speed is 1.0 m / min.
[0052] After spraying, the product is sent to a secondary drying device at a drying temperature of 80℃ for 10 minutes until the moisture content is below 3%. Finally, it is wound up at a speed of 1.2m / min and a tension of 60N to obtain a composite product of antibacterial unidirectional nonwoven fabric and absorbent paper, whose comprehensive performance meets the requirements of high-end care products.
[0053] Comparative Example 1: The difference from Example 1 is that the unidirectional flow-guiding nonwoven fabric did not undergo hydrophilic-water-repellent gradient finishing, and the amount of hydrophilic finishing agent adhering to the upper and lower surfaces of the fiber felt was the same, both at 5 g / m. 2 No unidirectional flow gradient was formed, but the remaining steps and parameters were completely consistent with those in Example 1.
[0054] Comparative Example 2: The difference from Example 1 is that the needle punching process of the unidirectional flow nonwoven fabric is changed to single needle punching, the needle punching frequency is 200 times / min, the needle punching depth is the total height of the fiber web, the number of needle punches is 5, and the multi-gradient needle punching process is not used. The remaining steps and parameters are completely consistent with Example 1.
[0055] Comparative Example 3: The difference from Example 1 is that the absorbent paper did not contain the self-made surface-modified superabsorbent resin, but only ordinary wood pulp paper was used without modification treatment. The remaining steps and parameters are completely the same as those in Example 1.
[0056] Comparative Example 4: The difference from Example 1 is that the composite molding only uses hot pressing, without adding hydrophilic adhesive, the hot pressing parameters remain unchanged, and the remaining steps and parameters are completely consistent with Example 1.
[0057] Comparative Example 5: The difference from Example 1 is that the fiber ratio of the unidirectional flow nonwoven fabric is the conventional ratio, namely 80 parts of hydrophilic modified polypropylene fiber, 20 parts of kapok fiber, and no polylactic acid fiber is added. The remaining steps and parameters are completely consistent with Example 1.
[0058] Comparative Example 6: The difference from Example 1 is that the improvement methods of Comparative Example 1 and Comparative Example 3 are used at the same time. That is, the unidirectional flow nonwoven fabric is not gradient-finished and the absorbent paper is not modified. The remaining steps and parameters are completely consistent with Example 1.
[0059] The following specific implementation methods are added to address the key technical details of this invention. Those skilled in the art can directly implement it according to the following specific parameters without any creative effort: Preparation method of surface-modified superabsorbent resin: Sodium acrylate-acrylamide copolymer resin is used as the matrix, and silane coupling agent KH-550 is used for surface modification. The copolymer resin and KH-550 are mixed at a mass ratio of 100:1, and the mixture is stirred at 60℃ for 30 min. After the reaction is completed, the mixture is dried and pulverized to 100 mesh to obtain surface-modified superabsorbent resin.
[0060] Specific implementation parameters of the gradient hydrophilic structure: The antibacterial hydrophilic finishing agent is applied using gradient impregnation treatment, and the amount of finishing agent adhering to the surface of the fiber felt is 8 g / m². 2 The surface finishing agent adhesion amount is 3g / m 2 By creating a hydrophilic gradient with a high hydrophilicity on the upper surface and a low hydrophilicity on the lower surface through the difference in the amount of adhesion between the upper and lower surfaces, a directional liquid conduction channel is constructed.
[0061] Specific process parameters for gradient needle punching: The fiber web is formed by four gradient needle punching passes, with a needle punching frequency of 200 times / min and a needle density of 1200 needles / m². 2 The first needle penetration depth is equal to the total height of the fiber web, and the needle penetration is performed 3 times; the second needle penetration depth is 11 / 12 of the total height of the fiber web, and the needle penetration is performed 5 times; the third needle penetration depth is 10 / 12 of the total height of the fiber web, and the needle penetration is performed 7 times; the fourth needle penetration depth is 9 / 12 of the total height of the fiber web, and the needle penetration is performed 9 times, thus forming a stable fiber density gradient.
[0062] The specific process ensuring a seamless composite interface involves a combination of hot-press lamination and hydrophilic adhesive textured coating, with a hydrophilic adhesive coating amount of 5 g / m². 2 The hot-pressing composite temperature is 130℃, the hot-pressing pressure is 0.2MPa, and the hot-pressing time is 10s, which makes the unidirectional flow-guiding nonwoven fabric and the modified absorbent paper tightly bonded together with no gaps at the interface.
[0063] Specific specifications of antibacterial components: The organosilicon quaternary ammonium salt in the antibacterial hydrophilic finishing agent is a cationic organosilicon quaternary ammonium salt with a molecular weight of 2000, and the hydrophilic amino silicone oil is a modified silicone oil with an ammonia value of 0.3 mmol / g, ensuring the antibacterial effect of the material.
[0064] Performance testing and results analysis: The composite products prepared in Examples 1-4 and Comparative Examples 1-6 were tested for unidirectional flow properties, water absorption and retention properties, composite strength, air permeability, antibacterial properties, and microbiological indicators according to relevant standards and the test methods set in this invention. All test samples were of the same specification, with 5 test points taken for each sample. The average value of the test results was used to ensure the accuracy and representativeness of the tests. The test standards referenced were T / CNITA09111-2023 group standard, GB / T5453, GB / T4744, GB / T24218.3, GB15979-2002, and other relevant standards. The specific test items, test methods, and test results are as follows.
[0065] Test items and test methods: (1) Unidirectional flow velocity: The simulated liquid test method was adopted. The simulated liquid was the simulated menstrual blood prepared in Appendix B of GB / T8939-2018. The temperature was controlled at 20±2℃. 10mL of simulated liquid was taken and dropped onto the surface of the unidirectional nonwoven fabric of the composite product. The time when the liquid completely penetrated into the absorbent paper and there was no liquid residue on the flow-guiding surface was recorded. This time is the unidirectional flow-guiding speed, with the unit being seconds. The shorter the time, the better the unidirectional flow-guiding performance.
[0066] (2) Longitudinal / lateral infiltration rate: Perform the test according to GB / T4744. Under the condition of water temperature 20±2℃, test the longitudinal and transverse liquid permeation velocities of the composite product, respectively, in mm / s. The faster the velocity, the better the permeation performance, which is used to help evaluate the uniformity of unidirectional flow.
[0067] (3) Water absorption ratio: The composite product was cut into 10cm×10cm samples using the immersion method. The samples were dried to constant weight and recorded as m1. Then, they were immersed in deionized water at 25℃ for 30 minutes. After that, the samples were taken out, the surface moisture was absorbed with filter paper, and the mass was recorded as m2. The water absorption ratio = (m2-m1) / m1, in g / g. The higher the value, the better the water absorption performance.
[0068] (4) Recirculation rate: Cut the composite product into 10cm×10cm samples, soak them in deionized water at 25℃ for 30 minutes, remove them and use filter paper to absorb the surface moisture. Then place a 500g weight on the sample surface and keep it for 10 minutes. Weigh the mass of water absorbed by the filter paper, which is the re-permeation amount in grams. The smaller the value, the better the water-locking performance.
[0069] (5) Composite peel strength: The test is carried out in accordance with GB / T 24218.3, using the strip method. The finished composite product is cut into a 10 cm × 5 cm sample, the unidirectional flow-guiding nonwoven fabric and absorbent paper are peeled off along the edges, and a tensile testing machine is used to test the maximum force during peeling, which is defined as the composite peel strength, with the unit N / 5cm. A larger value indicates better composite strength and less likelihood of peeling.
[0070] (6) Air permeability: The test is carried out in accordance with GB / T 5453, with a pressure drop of 200 Pa on both sides of the test specimen, to test the air permeability of the finished composite product, with the unit mm / s. A larger value indicates better air permeability, which ensures use comfort.
[0071] (7) Hydrostatic pressure: The test is carried out in accordance with GB / T 4744 under the conditions of a water temperature of 20±2°C and a water pressure rise rate of 6.0 kPa / min, with the unit kPa. A larger value indicates better liquid barrier performance.
[0072] (8) Antibacterial performance: The inhibition zone method is adopted to test the bacteriostasis rate of the finished composite product against Escherichia coli and Staphylococcus aureus, with the unit %. A bacteriostasis rate of ≥90% is deemed as qualified for antibacterial performance, and only Example 4 and Example 1 are tested as controls.
[0073] (9) Microbial indicators: The test is carried out in accordance with Appendix B of GB 15979-2002 to test the total bacterial colony count, Escherichia coli and Staphylococcus aureus. The result is qualified when the total bacterial colony count is ≤200 CFU / g, and Escherichia coli and Staphylococcus aureus are not detected.
[0074] The test results are shown in Table 1 below:
[0075] Analysis of test results: Based on the above test results, it can be seen that the composite products prepared in Examples 1-4 of this invention have better performance than those in Comparative Examples 1-6, highlighting the advantages of the core modification process of this invention. Example 1, as the basic benchmark, achieved the expected standards in all performance aspects: unidirectional flow rate of 8s, water absorption ratio of 45g / g, composite peel strength of 12.5N / 5cm, air permeability of 35mm / s, hydrostatic pressure of 6.2kPa, with no serious backflow or composite peeling issues. Microbiological indicators were all qualified, proving that the technical solution of this invention can be stably implemented. Example 2, based on Example 1, added bamboo fiber and optimized the needle-punching process, shortening the unidirectional flow rate to 7s, increasing the air permeability to 38mm / s, increasing the longitudinal penetration rate to 3.0mm / s, and decreasing the transverse penetration rate to 0.5mm / s. This indicates that the addition of bamboo fiber can effectively improve flow and air permeability, and the optimization of the gradient needle-punching process can further enhance the unidirectional flow effect. Example 3 optimized the absorbent paper modification process by adjusting the wood pulp ratio, additive proportion, and superabsorbent resin dosage. The absorbency increased to 58 g / g, and the rewetting decreased to 0.15 g, representing a 28.9% increase in absorbency and a 50% reduction in rewetting compared to Example 1. This demonstrates that the addition and optimized ratio of surface-modified superabsorbent resin can significantly improve absorbency and water retention performance, achieving a synergistic adaptation of flow and water retention. Example 4 optimized the composite molding process and antibacterial modification, further reducing the unidirectional flow rate to 5 seconds, increasing the composite peel strength to 15.3 N / 5 cm, raising the hydrostatic pressure to 7.2 kPa, and achieving an antibacterial rate of 95% / 94%. The overall performance was significantly improved, making it suitable for high-end nursing scenarios.
[0076] Comparison of the various comparative examples reveals that the absence of core modification processes or conventional treatment leads to a significant decrease in performance. Comparative example 1, without gradient hydrophilic finishing, experienced a unidirectional flow rate extended to 25 seconds, with the lateral and longitudinal penetration rates approaching each other, failing to achieve effective unidirectional flow and resulting in a rewetting amount of 1.2g. This demonstrates that gradient hydrophilic finishing is crucial for achieving unidirectional flow. Comparative example 2, without multi-stage gradient needle punching, saw its composite peel strength drop to 8.6 N / 5cm and air permeability to 32 mm / s, indicating that gradient needle punching effectively improves composite strength and air permeability. Comparative example 3, without modification of the absorbent paper, had a water absorption ratio of only 22g / g and a rewetting amount as high as 2.5g, failing to meet water-locking requirements. This proves that in-situ modification of the absorbent paper is the core for improving water absorption and water-locking performance. Comparative example 4, using only single hot-pressing composite, saw its composite peel strength drop to 5.2 N / 5cm, far lower than Example 1, demonstrating that combining hot pressing with adhesive composite significantly improves the bonding strength of the composite interface. Comparative Example 5, using a conventional fiber ratio, showed lower performance across all aspects compared to Example 1, demonstrating that a synergistic ratio of multi-component fibers can achieve synergistic performance improvement. Comparative Example 6, lacking both gradient finishing and absorbent paper modification, exhibited the worst performance, with a unidirectional flow rate of 32s, an absorbency of only 20g / g, and a rewetting rate of 3.2g. This further demonstrates the importance of the synergistic effect of the core modification process in this invention, highlighting the fundamental difference between this invention and existing technologies.
[0077] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention.
Claims
1. A composite material of unidirectional nonwoven fabric and absorbent paper, characterized in that: It is composed of a unidirectional nonwoven fabric layer and a modified absorbent paper layer; the unidirectional nonwoven fabric layer has a gradient structure with a high hydrophilicity on the upper surface and a low hydrophilicity on the lower surface; the modified absorbent paper layer contains a surface-modified superabsorbent resin; the two layers are combined by a combination of hot-pressing and hydrophilic adhesive.
2. The composite material according to claim 1, characterized in that: The raw materials for the unidirectional nonwoven fabric layer are kapok fiber, hydrophilic modified polypropylene fiber, and polylactic acid fiber. Based on a total raw material mass of 100 parts, the kapok fiber is 25-35 parts, the hydrophilic modified polypropylene fiber is 45-55 parts, and the polylactic acid fiber is 15-25 parts.
3. The composite material according to claim 1, characterized in that: The weight ratio of softwood pulp to hardwood pulp in the modified absorbent paper layer is 20:80-30:70; the surface-modified superabsorbent resin is a sodium acrylate-acrylamide copolymer resin modified with silane coupling agent KH-550.
4. A method for preparing the composite material according to any one of claims 1 to 3, characterized in that, Includes the following steps: (1) Preparation of unidirectional nonwoven fabric: the fibers are mixed, opened and combed into a fiber web, and then the fiber felt is obtained by four gradient needle punches. The fiber felt is then impregnated with an antibacterial hydrophilic finishing agent and dried. (2) Modification of absorbent paper: Wood pulp is crushed, ground and mixed into pulp, wet strength agent, softener and surface modified super absorbent resin are added, and modified absorbent paper is obtained by wet forming, pressing and drying. (3) Composite molding: The lower surface of the unidirectional nonwoven fabric is bonded to the upper surface of the modified absorbent paper, and the composite intermediate is obtained by hot pressing and bonding with a hydrophilic adhesive; (4) Finishing: The composite intermediate is shaped, trimmed, and rolled to obtain the finished product.
5. The preparation method according to claim 4, characterized in that: The fiber opening speed is 700-900 r / min, the opening time is 12-18 min; the carding speed is 2-4 m / min, and the carding spacing is 0.25-0.35 mm.
6. The preparation method according to claim 4, characterized in that: The acupuncture frequency for the four-level gradient acupuncture was 180-220 times / min, and the acupuncture needle density was 1200-1500 needles / m². 2 The depth of acupuncture decreases gradually, while the number of acupuncture points increases gradually.
7. The preparation method according to claim 4, characterized in that: The antibacterial hydrophilic finishing agent is composed of 25%-30% organosilicon quaternary ammonium salt, 30%-35% hydrophilic amino silicone oil, and 40% water by weight; the impregnation temperature is 40-50℃ and the impregnation time is 20-25 minutes.
8. The preparation method according to claim 4, characterized in that: The wood pulp is milled to a beating degree of 40-45°SR; the amount of surface-modified superabsorbent resin added is 8-15 parts of the total mass of the wood pulp.
9. The preparation method according to claim 4, characterized in that: The hydrophilic adhesive is a water-based polyurethane adhesive, applied using a textured coating method, with a coating amount of 3-7 g / m². 2 The hot-pressing temperature is 120-150℃, the hot-pressing pressure is 0.1-0.3MPa, and the hot-pressing time is 8-12s.
10. The preparation method according to claim 4, characterized in that: The composite intermediate is set at a temperature of 90-110℃ for 15-20 minutes and a winding tension of 50-60N.
